2020
DOI: 10.3853/j.1835-4211.30.2020.1757
|View full text |Cite
|
Sign up to set email alerts
|

Australian Museum surveys of the vertebrate fauna of Coolah Tops National Park, NSW

Abstract: Coolah Tops, c. 360 km northwest of Sydney, at the western end of the Liverpool Range, in central western New South Wales, is a fertile basalt plateau that rises to over 1000 m, and so is cooler and wetter than the surrounding drier and hotter western slopes. It represents a western outlier of tall moist montane forest and may therefore have served as a mesic refuge during arid climatic cycles. Despite its high biodiversity and biogeographical interest, Coolah Tops National Park and the surrounding area was ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The successful identification of some samples required extensive comparisons with bat reference samples held by the Australian Museum and vouchered specimen data from online databases (NCBI GenBank and BOLDSystems). During this work phylogenetic analysis of samples of N. gouldi from WA and eastern Australia were found not to be monophyletic and differed by a level of DNA sequence divergence greater than that found between some currently recognized microbat species (Eldridge et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The successful identification of some samples required extensive comparisons with bat reference samples held by the Australian Museum and vouchered specimen data from online databases (NCBI GenBank and BOLDSystems). During this work phylogenetic analysis of samples of N. gouldi from WA and eastern Australia were found not to be monophyletic and differed by a level of DNA sequence divergence greater than that found between some currently recognized microbat species (Eldridge et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…This paper arose from efforts to use a DNA bar-coding approach to confirm species identifications of microbat specimens sampled during Australian Museum fieldwork (Eldridge et al, 2020). The successful identification of some samples required extensive comparisons with bat reference samples held by the Australian Museum and vouchered specimen data from online databases (NCBI GenBank and BOLDSystems).…”
Section: Introductionmentioning
confidence: 99%
“…daedalus Thomas, 1915a in some respects and that the latter taxon is a likely composite of at least two species. Eldridge et al (2020) demonstrated that multiple species are likely included under "N. geoffroyi" as currently understood; see also Parnaby et al (2021). They found species-level differences in average divergence of mitochondrial genes (cytochrome B and cytochrome oxidase 1) between samples from eastern NSW and those from the Pilbara and southwestern Western Australia.…”
Section: Introductionmentioning
confidence: 94%
“…Measurements of an extensive series of N. geoffroyi from throughout Australia indicates that Tasmanian animals average larger than those from mainland Australian. Tasmanian specimens are excluded from further consideration here, given that mainland Australian "N. geoffroyi" is a composite of at least two species (Eldridge et al, 2020) and the taxonomic status of Tasmanian populations has not been assessed. Our analyses treat N. geoffroyi as one entity because we did not identify any obvious geographic or morphological groupings in the morphometric data.…”
Section: Nyctophilus Heran and N Geoffroyimentioning
confidence: 99%
See 1 more Smart Citation